Wireless Data Logger Instrument for Indoor Acoustic Quality Measurement Based on Noise Background, Sound Distribution and Reverberation Time - Ayu Afifah Al-Farzaq; Harmadi Harmadi; Elvaswer Elvaswer (Universitas Andalas, 2022)
A wireless data logger system measuring indoor acoustic quality was developed using a NodeMCU ESP8266 and microphone sensor KY-037. The acoustic quality is based on parameters of sound pressure level and reverberation time. The system consists of a transmitter unit and a receiver unit. The transmitter unit is equipped with a Microphone KY-037 sensor as a sound detector and NodeMCU ESP8266 as a microcontroller and serial communication with the database. The transmitter unit of this measuring instrument is set at predetermined position points in a room. The results of testing the sound pressure level have an error percentage of 2.09% compared to the Digital Sound Level Meter GM1356 tool. Comprehensive testing of the tool has sent and processed sensor measurement data wirelessly into the database. The processed data is displayed through a GUI web server in the form of a background noise average, an average of the reverberation time value, and a graph of the sound pressure level in the room.